2004
DOI: 10.1007/s11661-004-0047-2
|View full text |Cite
|
Sign up to set email alerts
|

Texture characterization of autogenous Nd:YAG laser welds in AA5182-O and AA6111-T4 aluminum alloys

Abstract: This article reports a study of texture characterization in Nd:YAG laser welds of AA5182-O and AA6111-T4 alloys. Electron backscattering diffraction (EBSD) in the scanning electron microscope was used to determine the texture. The determination was made as a function of thickness through the sample. The results show that the welds can develop significant texture. In particular, the columnar grains that grow from the base metal into the weld have a strong 001 texture along the direction of growth.The reduced we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 5 publications
(9 reference statements)
0
12
0
Order By: Relevance
“…For the weld metal, the overall texture intensity of the sample HWM and the sample TWM is 12.3% and 9.4%, exhibiting a relatively weak texture in the weld metal (see Figure 3b,d and Table 1). In general, the overall texture of the weld metal is basically decided by the orientations of the grains [25] in the columnar zone [19] and the weld metal zone having the equiaxed grains is likely to have an almost random texture, while brass, copper and S components are normally encountered in the deformation texture of fcc materials [20,26]. The present work conforms this and the brass, copper, S and Goss components are in presence in the weld metal, which suggests some similar texture components in the weld metal were formed as base metal during the laser welding.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For the weld metal, the overall texture intensity of the sample HWM and the sample TWM is 12.3% and 9.4%, exhibiting a relatively weak texture in the weld metal (see Figure 3b,d and Table 1). In general, the overall texture of the weld metal is basically decided by the orientations of the grains [25] in the columnar zone [19] and the weld metal zone having the equiaxed grains is likely to have an almost random texture, while brass, copper and S components are normally encountered in the deformation texture of fcc materials [20,26]. The present work conforms this and the brass, copper, S and Goss components are in presence in the weld metal, which suggests some similar texture components in the weld metal were formed as base metal during the laser welding.…”
Section: Resultsmentioning
confidence: 99%
“…Previous reports [19,27] have suggested that the welded joint could develop several major textures and strong texture might exist at the base metal, HAZ and columnar grain zone of the weld metal, whereas the grain orientation at equiaxed grain zone in the center of weld metal was relatively random. The present work also confirms that the original base metal structure has been eliminated and replaced by a very fine equiaxed grain structure in the weld metal.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The addition of lithium not only reduces the material density but also significantly increases the elastic modulus, thereby increasing the specific strength and stiffness of the alloys [1,2]. Among the various challenges facing the widespread use of Al-Li alloys in the aerospace sectors are the joining method selection and their impact on the mechanical properties of Al-Li weldment [3]. Arc welding of Al-Li based alloys has been comprehensively studied [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…However, the main defect of those blanks lies in that they consist of discrete thickness sections and may lead to stress concentrations in the weld lines or interfaces which result from the laser welding process [18,19]. Furthermore, the weld interface may contain complex microstructures with questionable ductility [27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%